1995
DOI: 10.1507/endocrj.42.753
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Regulates Rat Placental Type III lodothyronine Deiodinase Activity by Inducing Kinetic Changes Different from Those in the Same Isozyme in Rat Brain.

Abstract: Abstract. The kinetics of type III iodothyronine deiodinase (5-D) in rat placenta and brain and the role of phospholipids in enzyme activity were determined. Pregnant Sprague-Dawley rats were given either vehicle (control group) or T4 (15 jug/100 g bw/day; hyperthyroid group) from the 14th to the 21st day of gestation. Mitochondrial-microsomal fractions of the placenta and brain were used as the source of T4 5-D. Placental T4 5-D activity in the hyperthyroid group was increased when determined at 13 nM T4, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Previously, changes in D3 activity have been found to correlate strongly with changes in expression of Dio3 mRNA [49]; however, we found no evidence for the change in protein production being regulated at a transcriptional level. Moreover, one of the PredTox compounds (FP007SE) showed a transcriptional increase in Dio3 mRNA within the liver following high-dose treatment (Figure 6A).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Previously, changes in D3 activity have been found to correlate strongly with changes in expression of Dio3 mRNA [49]; however, we found no evidence for the change in protein production being regulated at a transcriptional level. Moreover, one of the PredTox compounds (FP007SE) showed a transcriptional increase in Dio3 mRNA within the liver following high-dose treatment (Figure 6A).…”
Section: Discussioncontrasting
confidence: 89%
“…In the rat, D3 activity is reduced in cases of hypothyroidism [28,49], although the extent of the change varies between tissues [20]. The observed reductions in T 3 and T 4 , along with the transcriptional down-regulation of Dio1 mRNA (Supplementary Figure S4 at http://www.biochemj.org/bj/453/bj4530071add.htm), which is known to be down-regulated in cases of hypothyroidism, indicated that the livers of the treated rats were in a hypothyroid state [17,50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that D3 mRNA levels increase in brain and placenta during hyperthyroidism and decrease during hypothyroidism (15)(16)(17). However, the mechanism of this regulation remains unknown.…”
Section: D3 Mrna Levels In Mouse Embryonic Fibroblasts (Mefs) From Trmentioning
confidence: 99%
“…TH regulates D3 expression at transcriptional level in several other systems (St Germain et al 1994, Van der Geyten et al 1999b). In the rat, D3 activity is increased in hyperthyroidism and decreased in hypothyroidism (Mori et al 1995, Escobar-Morreale et al 1997. TH and retinoic acid also upregulate D3 activity and mRNA in cultured glial cells (Esfandiari et al 1994).…”
Section: Mechanisms Regulating Type 3 Deiodinasementioning
confidence: 99%